O regime mexicano para contratos de hidrocarbonetos - Rivera , Luis J. Béjar; Martínez , Carlos A. Villanueva; Herrera Vaca , José Luis; Morales , José Iván Sánchez Aldana (Revista de Direito Administrativo e Infraestrutura | RDAI, 2024)
This work aims to describe the main contractual instruments in the hydrocarbon sector, presenting an overview of the state of the art in Mexico. As a secondary objective, it intends to provide readers with a better understanding of the Mexican legal situation.